Toward data-based clinical decision making for adults with challenging behavior using the Behavior Problems Inventory-Short Form (BPI-S). Issue 2 (3rd April 2018) - Bowring, Darren L.; Totsika, Vasiliki; Hastings, Richard P.; Toogood, Sandy
Abstract : Purpose: The Behavior Problems Inventory-Short Form (BPI-S) is a shorter version of the Behavior Problems Inventory-01. In this paper, BPI-S population norms are reported from a total administrative population of adults with intellectual disability (ID). To facilitate the use of the BPI-S in clinical services to assess behavior change, the purpose of this paper is to describe how to use BPI-S clinically significant and reliable change (RC) scores. Design/methodology/approach: Data were gathered on 265 adults with ID known to services. Proxy informants completed the BPI-S on challenging behaviors over the previous six months. Clinically significant cut-off values and RC scores were calculated using the Jacobson and Truax's (1991) method. Findings: BPI-S clinical reference data are presented to provide benchmarks for individual and group comparisons regarding challenging behavior. Examples demonstrate how to use clinical norms to determine change. Practical implications: Behavior change is a major goal of researchers and practitioners. Data from the present study can make the BPI-S a valuable tool for determining change in challenging behavior following service input or intervention. Originality/value: Whilst well used in research, the BPI-S may be less extensively used in practice. This present study provides data to enable researchers and practitioners to use the BPI-S more widely in assessing clinical outcomes, such as intervention research and service evaluation.